Screening of sweet and grain sorghum genotypes for green biomass production in different regions of Kazakhstan - Zhapayev, Rauan; Toderich, Kristina; Kunypiyaeva, Gulya; Kurmanbayeva, Meruyert; Mustafayev, Mustafa; Ospanbayev, Zhumagali; Omarova, Aiman; Kusmangazinov, Adil (Journal of Water and Land Development, 2023)
As the impact of global climate change increases, the interaction of biotic and abiotic stresses increasingly threatens current agricultural practices. The most effective solution to the problem of climate change and a decrease in the amount of atmospheric precipitation is planting extremely drought-resistant and high-yielding crops. Sorghum can grow in harsh conditions such as salinity, drought and limited nutrients, also it is an important part of the diet in many countries. Sorghum can be introduced in many zones of Kazakhstan. Plant height and yield of green plant biomass of 16 sorghum samples in arid conditions were determined based on a set of agrobiological characteristics for field screening. The height of the studied samples of grain sorghum was 0.47 ±0.03 m, and the height of sweet sorghum was much longer, reaching up to 2.88 ±0.12 m. Also, there was a strong difference in green biomass in cultivated areas under different soil and climatic conditions, the green biomass of sweet sorghum was 3.0 Mg∙ha –1, and in grain sorghum, it reached up to 57.4 Mg∙ha –1. Based on the data of the field assessment for various soil and climatic conditions, the following samples were identified for introduction into production: samples of sweet sorghum for irrigated and rainfed lands of the Almaty Region and in the conditions of non-irrigation agriculture of the Aktobe Region – a promising line ICSV 93046. For non-irrigation agriculture of the Akmola Region, genotypes of sweet and grain sorghum are ‘Chaika’, ‘Kinelskoe 4’ and ‘Volzhskoe 44’.